KARAKTERISTIK MORFOLOGI STROBILUS JANTAN DAN STROBILUS BETINA PADA PINNUS SP. DI KAWASAN TAHURA POCUT MERAH INTAN ACEH BESAR - Rais, Muhammad; Yunadya, Yunadya; Eriawati, Eriawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
Pine is a type of plant that can grow in various environmental conditions and soil contours. Pine plants can even grow on steep land contours, such as ravines or mountains. This study aims to identify and describe the morphological characteristics of male and female strobilus in Pinus sp. which is in the Tahura Pocut Merah Intan area, Aceh Besar. The research was carried out using an observational approach through direct observation of the strobilus morphology found at the research location. Samples of male and female strobilus were collected and analyzed to identify differences in shape, size and morphological structure of the two. The results showed that the male strobilus has a smaller shape with slimmer scales and a greenish yellow color, while the female strobilus is larger with wider scales and a reddish color. Other differences can be seen in the position and number of scales on each strobilus, as well as the distribution of pollination in the two types of strobilus. This research provides a deeper understanding of the morphological differences between male and female strobilus in Pinus sp. which is important to support conservation efforts and management of natural resources in the Tahura Pocut Merah Intan area, Aceh BesarKeywords: Morphology, male strobilus, female strobilus, Pinus sp., Tahura Pocut Meurah Intan.